2011
DOI: 10.1186/1471-2474-12-113
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of TGF-β1 stimulation of α-smooth muscle actin and extracellular matrix components by cyclic AMP in Dupuytren's - derived fibroblasts

Abstract: BackgroundMyofibroblasts, a derived subset of fibroblasts especially important in scar formation and wound contraction, have been found at elevated levels in affected Dupuytren's tissues. Transformation of fibroblasts to myofibroblasts is characterized by expression of alpha- smooth muscle actin (α-SMA) and increased production of extracellular matrix (ECM) components, both events of relevance to connective tissue remodeling. We propose that increasing the activation of the cyclic AMP (cAMP)/protein kinase A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 47 publications
1
60
1
1
Order By: Relevance
“…The palmar fascia fibrosis seen in DD is associated with excessive deposition of extracellular matrix (ECM) components including fibronectin [19]. DD tissues and cells have been reported to show increased expression of fibronectin type III extra-domain B ( FN 1-ED-B) and “oncofetal” fibronectin levels [34, 35] which prompted us to determine if PFD can play a role in reducing fibronectin levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The palmar fascia fibrosis seen in DD is associated with excessive deposition of extracellular matrix (ECM) components including fibronectin [19]. DD tissues and cells have been reported to show increased expression of fibronectin type III extra-domain B ( FN 1-ED-B) and “oncofetal” fibronectin levels [34, 35] which prompted us to determine if PFD can play a role in reducing fibronectin levels.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition or reversion of the myofibroblast phenotype to normal may mitigate disease progression and severity. Previous studies from our laboratory have shown that increasing cyclic AMP (cAMP) levels via forskolin (an adenylate cyclase (AC) activator) has potential to inhibit TGF-β-induced myofibroblast formation and accumulation of ECM components in DD-derived fibroblasts [19]. Overproduction of cAMP that can provide a means to blunt fibrosis has also been shown in cardiac and pulmonary fibroblasts [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, activated fibroblasts and myofibroblasts, which are characterized by the expression of α-SMA, can be stimulated and observed in fibrotic tissue [30]. Several studies have indicated that the expression of α-SMA may be regulated by different signaling pathways, e.g., the TGF-β, CTGF and cAMP/PKA pathways [31]. The immunoblot analyses revealed that the expression levels of both CTGF and α-SMA were increased following ANE treatment (Fig 4).…”
Section: Discussionmentioning
confidence: 99%
“…A higher level of α 2 integrin (p≤0.05, against internal control fascia) and α 5 integrin chains (p≤0.07, against external control fasica) has been observed in DD cord through fluorescence activated cell sorting 64 . Fibronectin , which is involved in the integrin signalling pathway, is elevated in DD, as shown by multiple studies at both mRNA and protein levels 27 6567. Isoforms of fibronectin, ED-A and ED-B, are found in the proliferative and involuational stage of DD 67.…”
Section: Integrin Signalling Pathwaymentioning
confidence: 95%